Government Information Dissemination During Public Health Emergencies: An Analysis of China's Experiences - Zhang, Yuye; Shan, Jiahao; Ye, Zheyou (Frontiers in Public Health, 2022)
Information disclosure is crucial in China’s official response to the COVID-19 pandemic. Since the early phase of the pandemic, the government's method of communication has relied heavily upon its analysis of information disclosed during past public health emergencies. This approach was proposed to better inform and prepare citizens during the crisis. This study aimed to study the effectiveness of China’s information disclosure by examining themes, interconnection, and timeliness of information as posted on the Weibo microblogging platform between January and April 2020. The Latent Dirichlet Allocation (LDA) topic model analysis for social networks revealed six main characteristics including a shift from 'scattered' to 'focused' communication. Three main themes surrounding experience were highlighted, namely social governance, medical expertise, and encouragement, although experiential knowledge disclosure was timelier than other topics. This study broadens the dimension and scope of empirical theory by examining government information disclosure practices and provides a reference for further research.